Pengaruh Pembelajaran IPA menggunakan Model Creative Problem Solving dengan Smartphone terhadap Kreativitas dan Inovasi Siswa - Rasyid Zuhdi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
This research aimed to analyze: (1) to describe the improvement from the ability of students’s creativity and innovation used learning based the creative problem solving by smartphone, and (2) to test the effect of learning based the creative problem solving by smartphone on creativity and innovation at student’s. Smartphone as a result of the progress of the digital era arre currently as instructional media collaborate with experimental learning model as an innovative and creative learning. This research was conducted on VII grade in 3 junior high school student’s at Kebumen with high, medium and low categories. The type of research was quasi experimental, used matching pretest-posttest control group design. The data retrieval technique was done by essay test. Data analysis used gain score and multivariate test. Research result: (1) based on the analysis in high category schools has obtained N-Gain values ??0.82 included in the high category, in medium category schools has obtained N-Gain values 0,8 1 included in the high category, and in low category schools has obtained N-Gain values 0,83 included in the high category.( 2) all of the category schools based on the multivariate test result that was used Hotelling's Trace showed a significance value <0.05, which gives an H0 rejected. Conclusion: all of the category school used learning based the creative problem solving by android have improvement and significant effect on the ability of student’s creativity and innovaion at Kebumen.. Keywords: creative problem solving, android, metaknowledge